PENERAPAN METODE PEMBELAJARAN WHOLE BRAIN TEACHING PADA MATERI MAPLE - Irsyadi, Mohamad Khafid; Sari, Ayu Silvi Lisvian (Institut Agama Islam Negeri (IAIN) Tulungagung, 2020)
This research is a Classroom Action Research which aims to describe the application of Whole Brain Teaching learning method to Maple material. The steps of the learning model are as follows: (1) Yes-Class, the lecturer observes the readiness of students in starting the lecture by saying